Diagnosis Of Pulmonary Tuberculosis In Children Systematic Literature Review - Sara Fadila; Tri Yunis Miko Wahyono (Jurnal EduHealth, 2023)
Tuberculosis (TB) is one of the top ten causes of death caused by infectious agents in Indonesia. In children, more than 96% of TB-related deaths are due not receiving anti-TB treatment, this is significant challenges to diagnosing TB in children. This study aims to analyze the methods of diagnosing TB in children. The research design used a systematic literature review which summarized and compared as many as 12 studies published through Pubmed and Sciencedirect in 2010-2022 concerning methods of diagnosing TB in children. Descriptive analysis showed that the subjects were male with an average age of 4.5 years. Diagnostic enforcement of TB in children found that the scoring system was the most widely used method to diagnosing TB in children with a high sensitivity and specificity, sensitivity and specificity using the modified Edwards Score was 93.3% and 95%. Furthermore, the PCR method by detecting the IS6110 gene using gastric lavage specimens showed sensitivity and specificity was 100% and 98.18%. The QFT-GIT diagnostic method showed a sensitivity of 82.6%, and Xpert MTB/RIF of 76%.